Measles virus-specific IgD antibodies in patients with subacute sclerosing panencephalitis. - Luster, M I (1976)
Indirect immunofluorescent analysis revealed that sera from five patients with subacute sclerosing panencephalitis possessed IgD antibodies directed against measles virus components in persistently infected HeLa cells. IgD levels in these sera were within the normal range. Control studies indicated that the reaction was specific for measles virus. The detection of IgD measles antibodies in these patients suggested that IgD may be involved in the pathogenesis of this viral disease.